Pendidikan Karakter Berbasis Kurikulum Terintegrasi di Perguruan Tinggi Agama Islam - Khalid Rahman (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
This study departs from an integrated curriculum problem in higher education which has not found a clear formulation according to the direction of character formation. In the integrated curriculum, there is a comprehensive model to the practical level to shape the character of students. Today's universities are almost having trouble producing graduates with character. The integrated curriculum offers an integrated and complex educational concept in developing student potential. With the character education model based on an integrated curriculum, it is hoped that it will be a solution to the concerns of education practitioners facing the decline in the character of higher education graduates. This paper explains that: (1) The concept of integrated curriculum-based character education carried out in tertiary institutions consists of the conception of an integrated vision and mission, institutional integration, curriculum integration, and learning according to the model both within single disciplines, across several disciplines, and inside the mind. of the learners; (2) Integrated curriculum-based character education uses a rational and deductive interaction approach to divide roles between leaders, employees, and lecturers; (3) methods and strategies in integrated curriculum-based character education in the classroom, by prioritizing problem-solving methods, project methods, unit teaching, inquiry, discovery, and thematic approaches; (4) evaluation of integrated curriculum-based character education.